2020
DOI: 10.4314/rjmhs.v3i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Functional Health Literacy and Self-Care Behaviors Among Type 2 Diabetic Patients at a University Teaching Hospital in Kigali

Abstract: Background Type 2 Diabetes Mellitus (T2DM) is a significant health burden in high-income countries and emerging in sub-Sahara African countries, including Rwanda. Prevention and treatment of T2DM are imperative and need to focus on functional health literacy and self-care practices among people with diabetes. Objective To determine if functional health literacy is associated with self-care behaviors among T2DM patients. Method This study was a descriptive cross-sectional design co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
2
3
1
Order By: Relevance
“…The study ascertained that high diabetic health literacy among the respondents was 30.3% (95% CI 25.4, 34.8). This finding was higher than the study conducted on the urban population of Bangladesh (24%) [ 18 ], Jamaica (13.6%) [ 2 ], Iran(18.2%) [ 19 ], and Rwanda (14.3%) [ 4 ] respectively. This discrepancy might be due to variations in the tools utilized, socio-cultural and geographical differences.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The study ascertained that high diabetic health literacy among the respondents was 30.3% (95% CI 25.4, 34.8). This finding was higher than the study conducted on the urban population of Bangladesh (24%) [ 18 ], Jamaica (13.6%) [ 2 ], Iran(18.2%) [ 19 ], and Rwanda (14.3%) [ 4 ] respectively. This discrepancy might be due to variations in the tools utilized, socio-cultural and geographical differences.…”
Section: Discussioncontrasting
confidence: 56%
“…According to International Diabetes Federation report in 2019, the number of diabetic patients will rise to 700 million by 2045 [ 3 ]. In sub-Saharan Africa (SSA), DM is predicted to increase quickly, rising by 80% over 20 years, and will affect around 18.7 million Africans by the year 2025 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Educational status also signi cantly associated with diabetic health literacy. This nding is consistent with study done in Iran, Rwanda and China (27,29,34), that low level of educational status was associated with low diabetic health literacy. The result is also consistent with a study from Gondar, Ethiopia in which participants with greater educational status had a high mean score of diabetic health literacy (21).…”
Section: Discussionsupporting
confidence: 93%
“…The study nding showed that only 22.4% (95% CI 19.2, 25.9) of the participants had high diabetic health literacy level. This nding is higher than study in Iran (18.2%) (27), Mexico (17.6%) (28) and Kigali Rwanda (14.3%) (29). The discrepancy might be due to difference in tools utilized, study populations (those studies conducted in type 2 diabetic patients) and sociocultural variation.…”
Section: Discussionmentioning
confidence: 63%
“…The study findings that most of participants reported poor Physical Activity level, followed by those who reported fair level, and those who reported good level. This finding is consistent with (6) who concluded that most of study participants have low level of physical activity. More than two-fifth reported good Risk Reduction level (n = 148; 41.3%), followed by those who reported fair level (n = 137; 38.3%), and those who reported poor level (n = 73; 20.4%).…”
Section: Discussionsupporting
confidence: 92%